Symptomatic Fluid Drainage: Peritoneovenous Shunt Placement - Yarmohammadi, Hooman; Getrajdman, George I. (Seminars in Interventional Radiology, 2017)
Ascites causes significant discomfort and has negative impact on patient's quality of life. Medical therapies including dietary restriction and diuretics are successful in only 40 to 44% of patients with malignant ascites and repeated paracentesis only provides temporary symptomatic relief. Therefore, a more permanent solution is necessary. Indwelling catheters or peritoneovenous shunt placement can provide more permanent symptomatic relief and improve patients' quality of life. Unlike indwelling catheters, peritoneovenous shunts do not limit patients' life style and therefore should be offered as first option in patients who are good candidates. Denver shunt (CareFusion-BD Worldwide) is the current available peritoneovenous shunt. In this article, the indications, contraindications, technical aspects of shunt placement, and techniques to prevent postprocedure complications will be discussed.
Keywords: ascites; malignant ascites; peritoneovenous shunt; Denver shunt; chylous ascites